Meta-Analysis: The Effect of Teaching Media towards Students English Vocabulary Mastery - Yudiramanda, Shofiyah Dinda; Suhandoko, Farsya Shabira; Sulhan, Muhammad (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
This study conducts a meta-analysis to evaluate how different teaching media affect students' English vocabulary mastery. This research uses a quantitative method by conducting meta-analysis to review 20 quantitative experimental articles published between 2018 and 2024. The research aims to give a detailed understanding of the impact of various media on vocabulary learning. The study finds that interactive and engaging media, such as games, songs, and applications like Duolingo and